+0  
 
0
43
4
avatar

1. 5x + 3 = 7x – 1. Find x

a. 1/3
b. ½
c. 1
d. 2

 

 

 

2. 5x + 2(x + 7) = 14x – 7. Find x

a. 1
b. 2
c. 3
d. 4

 

 

 

 

3. 12t – 10 = 14t + 2. Find t

a. -6
b. -4
c. 4
d. 6

 

 

 

4. 5(z + 1) = 3(z + 2) + 11 Solve for Z

a. 2
b. 4
c. 6
d. 12

 

 

i dont get 2 and 3

 Sep 3, 2020
 #1
avatar+1035 
+1

From now on, only one question per post. Also, if you don't get 2 and 3, why post 1 and 4?

 

2. 5x + 2(x + 7) = 14x – 7. Find x

a. 1
b. 2
c. 3
d. 4

 

If you really don't get it, let me tell you one thing. Since this is multiple choice, use trial and error. If you are on a test, nobody can help you with anything. So, if you don't get a multiple choice math question (or grammar) use trial and error.

 

But that would be pointless if I used it, because I know how to solve it, and you won't learn.

 

To begin, we distribute the 2 in 2(x + 7)

 

5x + 2(x + 7) = 14x – 7

5x + 2x + 14 = 14x -7

7x + 14 = 14x -7

 

Now, we need to isolate the x. First, subtract 14x from both sides. Then, subtract 14 from both sides.

 

7x + 14 = 14x -7

-7x + 14 = -7

-7x = -21

x = 3

 

3. 12t – 10 = 14t + 2. Find t

a. -6
b. -4
c. 4
d. 6

 

Here is what I don't get. If you could solve one, then you can solve 3. If you could solve 4, then you can solve 2. 

 

Anyways, to begin, we want to isolate the t. The first natural process it to subtract 12t from both sides:

 

12t – 10 = 14t + 2

-10 = 2t + 2

 

Subtract 2 from both sides:

 

-12 = 2t

 

Divide by 2:

 

-6 = t

 

I solved both for you. Next time you post more than one question, know that you won't get a reply. (most likely)

 

I hope you understand now.

 

:)

 Sep 3, 2020
edited by ilorty  Sep 3, 2020
 #2
avatar
0

 

ilorty, I'm not the original poster, but I need clarification 

 

       how do you get from     5x + 2(x + 7) = 14x – 7  

                                 to     5x + 10x + 14 = 14x -7   

 

I was thinking it should be    5x + 2x + 14 = 14x – 7   

 

Please help.  

.

Guest Sep 3, 2020
edited by Guest  Sep 3, 2020
edited by Guest  Sep 3, 2020
 #3
avatar+1035 
0

Oh, you are right! I just made a silly mistake...

ilorty  Sep 3, 2020
 #4
avatar
0

1/       5x + 3 = 7x -1

          -2x = -4 

           -x = -2 | *-1

           x = 2

 

2/       5x +2(x + 7) = 14x - 7

          5x + 2x +14 = 14x - 7

          -7x = -21

          -x = -3 | *-1

           x = 3

 

3/        12t - 10 = 14t + 2

            -2t = 12

             t = -6

 

4/          5(z + 1) = 3(z + 2) + 11

             5z + 5 = 3z + 6 + 11

             2z = 12

              z = 6

 Sep 3, 2020

57 Online Users

avatar
avatar
avatar
avatar